(untitled) - Mauk, John; Metz, John (Boston, MA, 2007)
Includes index.; Canada-Vietnam Education Network
Keywords: English language -- Rhetoric -- Handbooks, manuals; Manners and customs -- Problems, exercises; Report writing -- Handbooks, manuals; Readers -- Manners and customs